Making Nordic historiography : connections, tensions and methodology, 1850-1970 - Haapala, Pertti, 1954-; Jalava, Marja, 1965-; Larsson, Simon (New York : Berghahn, 2017)
Is there a “Nordic history”? If so, what are its origins, its scope, and its defining features? In this informative volume, scholars from all five Nordic nations tackle a notoriously problematic historical concept. Whether recounting Foucault's departure from Sweden or tracing the rise of movements such as “aristocratic empiricism,” each contribution takes a deliberately transnational approach that is grounded in careful research, yielding rich, nuanced perspectives on shifting and contested historical terrain.
Sisältää bibliografisia viitteitä ja hakemiston.
Keywords: 1800-luku; 1900-luku; historiankirjoitus; historiantutkimus; metodologia; tutkimushistoria; oppihistoria; historiantutkijat; Scandinavia -- Historiography; Pohjoismaat